Do cedro à seringueira - memórias da comunidade de Sírio-Libanesa no Amazonas - Daou, Geórgia Pozzetti (2021)
This research focuses on the memories of Syrian-Lebanese descendants in Amazonas, seeking to give visibility to the participation of these immigrants in the development of Amazonian society. We consider that the memories of the elders are important links for the cultural continuity of a people, therefore, ten people were selected to participate in the study, considering they are third generation, over sixty years old and who are part of the same social network, formed at the time of the first immigrants. The methodology used refers to bibliographic research, which collaborates in the understanding of the migratory movements of the Syrian-Lebanese to Brazil; and oral history, which, through interviews, enables the (re) visitation of shared memories. Revealing these shared narratives provides an overview of how each participant sees the immigration of their ancestors and the continuity of Syrian-Lebanese culture today. In the composition of this dissertation, in addition to the narratives, the personal collections of the interviewees participate, revealing how they act in the constitution of memories and in the recognition of Syrian-Lebanese origins. The survey was conducted in the years 2019 and 2020, and the interviews were applied by telepresence, according to the Covid-19 guidelines for social isolation. To close this study, it is considered that the interviewees' memories still carry elements that lead them to be recognized as Syrian-Lebanese, as well as revealing the desire for the continuation of these memories to the new generations, even though the culture of origin is affected by culture place.